Metastatic Colorectal Cancer Resembling Severe Preeclampsia in Pregnancy - Raminder Kaur Khangura; Charanpreet Kaur Khangura; Anagha Desai; Gregory Goyert; Roopina Sangha (Case Reports in Obstetrics and Gynecology)
Although colorectal cancer (CRC) is the third most common cancer in women, it is a rare malignancy in pregnancy. Symptoms of CRC such as fatigue, malaise, nausea, vomiting, rectal bleeding, anemia, altered bowel habits, and abdominal mass are often considered typical symptoms of pregnancy. Many cases of CRC are diagnosed in advanced stages due to missed warning signs of CRC, which may be misinterpreted as normal symptoms related to pregnancy. This report reviews 2 cases of CRC diagnosed within a 4-month interval at our institution. Both cases were initially thought to be atypical presentations of preeclampsia. Prenatal history, hospital course, and postpartum course were reviewed for both patients. CRC is often diagnosed at advanced stages in pregnancy. Common physiological symptoms of pregnancy should be scrutinized carefully and worked up appropriately, especially if symptoms remain persistent or increase in intensity or severity.